Technical workshop report: Empowering financial intermediaries for climate-smart financing: Accelerating climate-smart horticulture in Ethiopia - Derenoncourt, Marie; Tesfaye, Lidya; Mebrat, Wondwossen Worku; Wamicwe, Peter; Burra, Dharani Dhar; Grosjean, Godefroy; Yaregal, Yodit Seyoum (2025)
As climate change intensifies, Ethiopia’s agriculture sector, largely composed of smallholder farmers dependent on rain-fed systems, faces growing threats from erratic rainfall, prolonged droughts, rising temperatures, and increasing input costs. The horticulture sector, a rapidly growing contributor to Ethiopia’s agricultural GDP and a key source of rural employment and export revenue, is particularly vulnerable due to its high sensitivity to climate variability and reliance on perishable, high-value crops. Despite its importance, the sector remains underserved by financial systems, with limited access to credit, weak climate risk integration, and low levels of tailored financial product development. This technical report highlights the key outcomes of a workshop held on May 29–30, 2025, in Addis Ababa, Ethiopia, under the Accelerating Climate-Smart Horticulture (ACT-H) initiative. The event convened 39 participants from 15 financial institutions and seven technical and policy organizations. Led by the CGIAR Hub for Sustainable Finance (ImpactSF), the Alliance of Bioversity International and CIAT, the International Water Management Institute, and Precise Consulting, the workshop provided intensive, hands-on training on climate risk assessment tools, including the ImpactSF Analyzer. The sessions also delved into practical approaches for climate-adjusted credit design, bundled product developments such as integrating insurance, inputs, and advisory services and blended finance structuring tailored specifically to the needs of horticultural enterprises. These interactive sessions aimed to build the capacity of financial institutions to integrate climate considerations into their lending portfolios and to support the resilience of high-value horticultural value chains. Complementing the workshop, the report draws on a national survey of 37 financial institutions to identify key gaps in climate-smart lending practices. These include limited horticulture-specific risk profiling, the prevalence of short-term and inflexible loan products, and weak technical partnerships that hinder the development of innovative financial solutions. Building on both the workshop and the survey findings, the report documents several actionable outcomes, including the co-design of four prototype financial products targeted at prioritized horticultural value chains. In general, the report demonstrates how the use of climate data-driven tools, institutional learning, and cross-sector collaboration can help strengthen Ethiopia’s financial ecosystem, laying the groundwork for inclusive, climate-resilient agricultural finance that is responsive to the specific needs of the horticulture sector amid a changing climate.